Effect of valproic acid, a histone deacetylase inhibitor, on cell death and molecular changes caused by low-dose irradiation - Záskodová, Darina; Rezácová, Martina; Vávrová, Jirina; Vokurková, Doris; Tichy, Ales (Annals of the New York Academy of Sciences, 2006)
Valproic acid (VA), a histone deacetylase inhibitor (HDACI), in vitro induces differentiation of promyelocyte leukemia cell (HL-60) and proliferation arrest and apoptosis of various leukemia cell lines. In MOLT-4 cells (human T lymphocyte leukemia) the cell cycle arrest is caused by 2 mM VA, while 4 mM VA induces mainly apoptosis. In our work we studied effect of VA on molecular mechanisms responsible for cell cycle arrest (2 mM VA) or apoptosis induction (4 mM VA). The aim of our article was to evaluate a cotreatment by low (cytostatic) concentrations of VA with ionizing radiation and an effect of this combination on apoptosis induction in tumor cells MOLT-4. We prove that 24-h long incubation with VA causes acetylation of histones H3 and H4 in concentration-dependent manners. During first hours after the beginning of cultivation with VA in both studied concentrations (2 and 4 mM) an increase of p53 and its phosphorylation on serine 392 is detected, as well as a phosphorylation of Mdm2 on serine 166. After 8 and 24 h after the beginning of cultivation with 2 mM VA we detect p21, which is not observed after exposure to 4 mM VA. Cleavage of lamin B to 46 kDa fragment as an indicator of apoptosis was apparent after 24-h long incubation with 4 mM VA. In this article we prove radiosensitizing effect of VA. After 3-days long cultivation of cells with 2 mM VA the D(0) value decreased from 0.7 to 0.2 Gy. Also the EC70 value fell from 0.97 to 0.38 mM when the cells were irradiated with a dose of 1 Gy before the continual cultivation with VA. Continual cultivation of MOLT-4 cells irradiated by the dose of 1 Gy with VA caused during 14 days after irradiation significant increase of apoptotic cells in comparison to the cells exposed to only one factor. As a conclusion it can be postulated that continual exposure of MOLT-4 cells to VA increases apoptosis and decreases colony-forming capacity of the cells irradiated with small dose of radiation.
Keywords: apoptóza; nádorové buněčné linie; leukemie T-buněčná; Valproic Acid; Cell Line, Tumor; Humans; Leukemia, T-Cell; Histone Deacetylase Inhibitors; záření gama; vztah dávky záření a odpovědi; lidé; Gamma Rays; inhibitory histondeacetylas; Dose-Response Relationship, Radiation; Apoptosis; kyselina valproová